2004
DOI: 10.1002/pat.434
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and ionic conductivity of a polysiloxane containing quaternary ammonium groups

Abstract: A novel quaternary ammonium salt, polysiloxane containing quaternary ammonium groups, was designed and synthesized. Thermogravimetric results showed that the polymer maintained stable below 250°C. Ambient conductivities higher than 10−4 S cm−1 could be observed when appropriate amounts of suitable plasticizers were incorporated into the present quaternary ammonium salt. A dye‐sensitized solar cell fabricated using a plasticized electrolyte showed a fill factor of 0.50 and an energy conversion efficiency of 7.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 13 publications
2
54
0
1
Order By: Relevance
“…A number of other membrane materials have been reported for application in DMAFCs, such as polysiloxane containing quaternary ammonium groups [107], aminated poly(oxyethylene) methacrylates [108], quaternised polyethersulfone Cardo [109], and quaternised poly(phthalazinon ether sulfone ketone) [110]. The poor stability of these materials in hydroxide electrolytes limited their further application in DMAFC.…”
Section: Cation Exchange Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of other membrane materials have been reported for application in DMAFCs, such as polysiloxane containing quaternary ammonium groups [107], aminated poly(oxyethylene) methacrylates [108], quaternised polyethersulfone Cardo [109], and quaternised poly(phthalazinon ether sulfone ketone) [110]. The poor stability of these materials in hydroxide electrolytes limited their further application in DMAFC.…”
Section: Cation Exchange Membranesmentioning
confidence: 99%
“…The maximum power density of 12 mW cm −2 was achieved with a mixed media: 1N KOH in anode and 1N H 2 SO 4 in cathode. Sung et al [107] developed a micro fuel cell using non-noble metal catalysts in alkaline media. The fuel cell was designed with both electrodes not facing each other, but being in-plane.…”
Section: Performance Of Daafcmentioning
confidence: 99%
“…However on Pt (100) the oxidation of methanol in NaOH was reported to be less active than in carbonate and bicarbonate solutions. FTIR data showed that CO is weakly adsorbed on Pt(111) compared with Pt (110) and Pt(100) [52]. Figure 13.3 shows cyclic voltammograms recorded for a platinized electrode at 60 C in 0.5 M solutions of NaOH, Na 2 CO 3 and NaHCO 3 .…”
Section: Effect Of Ph and Electrolytementioning
confidence: 99%
“…When the operational environment is alkaline, AMFCs have advantages of faster electrokinetics, lower fuel crossover, reduced CO poisoning, and use of non-precious metal catalysts such as silver, nickel and perovskite [2]. To date, much efforts have been taken to develop various types of AEMs based on quaternized polymers such as polysiloxane [3] and radiation grafted [VPSIm][OH] [4]. In this article, a new type of alkaline anion-exchange membrane was proposed based on cross-linking chitosan (CS) and poly[(3-methyl-1-vinylimidazolium methyl sulfate)-co-(1-vinylcaprolactam)-co-(1-vinylpyrrolidone)] composite (CS/PMVMS-co-VC-co-VP).…”
Section: Introductionmentioning
confidence: 99%